Сучасне застосування металевих сплавів для автомобілебудування - Гнатуш, В.А.; Дорошенко, В.С. (Physico-technological Institute of Metals and Alloys, 2023)
Vehicle manufacturing is at the forefront of the global world economy and is the forefront of competition from both economically advanced countries and powerful companies in the industry that are among the most profitable in the engineering sector. The article presents an analysis of the market for high-strength iron and carbon alloys for the automotive industry with a view to further developing this industry in Ukraine. In addition, off-road vehicles are required for defense purposes. The brands and chemical compositions of the alloys used by the world's most advanced companies in car designs are described. The decrease in the use of rolled steel will be offset by an increase in the use of rolled steel and castings made of aluminum alloys, which is fueled by the upward trend in electric vehicle output. Among the new materials is isothermally hardened austempered ductile iron (ADI), which has high foundry properties and durability at a lower cost of processing than steel. ADI mainly produces crankshafts and camshafts, gears, suspension brackets, impellers, valve housings, compressor housings. ADI has a high damping ability, which makes the parts absorb 2–5 times more energy than steel parts, so noise levels are reduced by about 8–10 decibels when used in gearboxes. Such information may be useful to designers, founders and metallurgists who provide the design, selection of materials and technology for the manufacture of metal billets and parts of vehicles, taking into account the reduction of their weight and pollution from their operation, as well as teachers and students of transport specialties, specialists in the utilization of metals of old cars to account for the composition of metals and subsequent blending in their melting and heat treatment of parts with advanced properties.